Populaion of India: 1991 census results and methodology - Bose, Ashish (Delhi, 1991)
The provocation for bringing out this book so hastily lies in my inability to cope with requests for exclusive interviews and 'popular' articles for the press, commenting on the first results of the 1991 Census which have just been released by the nsus Commissioner (25 March 1991). Author's, therefore, thought of putting together a simplified set of key tables from Census Paper No. 1 of 1991, along with a series of articles which he had written for The Financial Express, prior to the publication of census results, where he had discussed the methodology of the Census. This is not a research monograph.
Keywords: Demography